Politics of Defection and its Implications on Nigeriaas Democracy (Global Journal of Human-Social Science, 2017)
This study examines the politics of defection and its implications on Nigeria s democracy Nigeria s return to democracy in 1999 ushered in a great hope of democratic dividend and heralded a rare opportunity for the country to launch a new democratic strategy after years of military dictatorship The emergence of multiparty democracy in Nigeria since 1999 has been seen as a major breakthrough in the democratic process However the way and manner politicians in Nigeria defect from one party to the other has not only constituted democratic nuisance but has continued to raise serious concern among political observers and participants in Nigeria This have lend credence to lack of clear ideology and manifesto among political parties in Nigeria The issue of defection has been one of the major bane of democratic process in Nigeria
Keywords: democracy; defection; political culture; political party; political socialization